Southern Perspectives : Being a Southeast Asian Doctoral Student in Foreign Lands - Allotta, Elizabeth, (Educational Research E-Books Online, Collection 2026., 2026)
This volume is a collection of the stories of eight international students from Southeast Asia who journeyed to undertake doctoral studies in an Australian university. Each author shares the academic and cultural challenges of living and studying in a foreign country and adjusting to different cultural and social contexts, including the drivers, motivators, personal and familial expectations of undertaking doctoral studies in a foreign land, their changing sense of self and identity on their journey, and the impact of being separated from family, friends, and familiar supports. Insights are gained into the social, cultural and familial experiences that challenge doctoral students and their family members. Contributors are: M. Maksud Ali, Elizabeth Allotta, Brent Bradford, Danwei Gao, Huan Yik Lee, Yifie Liang, Muhammad Ali Musofer, Garth Stahl, Aaron Teo and Preeti Vayada.